PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR LURAH SANUR KOTA DENPASAR - I Made Artha Putra Duwipayana; I Ketut Setia Sapta; I Gede Rihayana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
This study aims to analyze the effect of the work environment and workload on employee performance at the Sanur Village Head Office, Denpasar City. This study uses the independent variable, namely the work environment and workload and the dependent variable, namely employee performance. The population used in this study were all employees, totaling 35 employees. The method of determining the sample in this study is the saturated sample method where all members of the population will be used as a sample of 35 employees. The analytical tool used is multiple linear regression analysis. Based on the analysis results show that the work environment has a positive and significant effect on employee performance. This means that the better the work environment, the better the employee's performance, and conversely, the lower the work environment, the lower the employee's performance. Similarly, workload has a positive and significant effect on employee performance. This means that the better the workload, the employee's performance will also increase, and vice versa, the decrease in the workload will have an impact on the decrease in employee performance as well.